THE RELATIONSHIP BETWEEN ANEMIA AND ANXIETY DISORDERS AMONG ADOLESCENT GIRLS IN BEKASI DISTRICT, INDONESIA: A CROSS-SECTIONAL STUDY - Utami Putri Kinayungan (Journal of Community Mental Health and Public Policy)
Background: Anxiety disorders are major mental health problem in Indonesia. In addition, the prevalence of anemia in adolescents is still high. Research shows that low iron levels can increase the risk of mental disorders, including anxiety disorders. Many studies have linked anemia to depressive symptoms, but research on anxiety disorders has not been widely studied. Purpose: to analyze the relationship between anemia and anxiety disorders in female adolescents. Methods: Quantitative research with a cross-sectional design conducted in three distinguished public schools in Bekasi Regency. The number of samples was 173 female adolescents selected using purposive random sampling techniques with inclusion criteria of being willing to provide blood samples, female students aged 15-18 years, and residing in Bekasi Regency. The exclusion criteria included students who were on a diet and consuming antidepressant medications. Anemia status was measured by Quick Check HB and anxiety disorders were assessed using the Depression Anxiety Scale (DASS 42) questionnaire. Results: Anemia in female adolescents was found to be 31.2%. Anxiety disorders were found to be 78.6%. The Bivariate test showed that there was no relationship between anemia status and depressive disorders (p-value = 0,167). Conclusion: There is a relationship between anemia status and depressive disorders in adolescents.